Risk‐Reducing Gender‐Affirming Mastectomy: Unique Considerations in BRCA - Bailey N. Johnson; Ivan Hadad; Aladdin H. Hassanein; Carla S. Fisher (Clinical Case Reports)
ABSTRACT Individualized breast cancer risk assessment should be considered for transmasculine patients pursuing gender‐affirming mastectomy to identify and educate high‐risk patients about the option for risk‐reduction gender‐affirming mastectomy. This reduces oncologic risk while achieving the desired cosmetic outcome, ultimately enhancing preventative care provided to an underserved population.